Intervention of Pregnancy Exercise with A Spiritual Mindfulness Approach Based on Breathing Exercise on Anxiety - Ranti Lestari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Primigravida pregnant women in their third trimester often feel anxious and experience sleep disturbances. Hormonal changes can also trigger anxiety, which can have a negative impact on the health of the mother and baby as well as on the delivery process. Pregnancy exercises with a spiritual mindfulness approach based on breathing exercises are expected to be a good alternative in overcoming anxiety in pregnant women. Determining the effectiveness of pregnancy exercise interventions using a spiritual mindfulness approach based on breathing exercises on the anxiety levels of primigravida pregnant women in their third trimester in facing childbirth. The study used a quasi-experimental design with a pre- and post-test with control group. The sample consisted of 32 pregnant women divided into two groups, namely 16 respondents in the intervention group and 16 respondents in the control group, with sampling using purposive sampling technique. Data collection was conducted using the PRAQ-R2 anxiety questionnaire. The questionnaire was proven to be valid and reliable, with a Cronbach's Alpha value of 0.85 for the total scale and 0.77–0.90 for the subscales. Data analysis using the t-test. There was a significant change before and after the intervention of pregnancy exercises on the anxiety levels (p value = 0.001) of primigravida pregnant women in their third trimester in facing childbirth. There were significant changes before and after the intervention of pregnancy exercises with a spiritual mindfulness approach based on breathing exercises on anxiety levels. It is hoped that pregnancy exercises with a spiritual mindfulness approach can be incorporated into antenatal care services to improve the mental health of pregnant women.